The problem of applying the text of Article 103 of the 2020 constitutional amendment - Drid, Kamel; Rais, Amina (Journal of Human Sciences, 2022)
Article 103 of the 2020 constitutional amendment included two assumptions about the possibility of government leadership. It may be led by a Prime Minister if the legislative elections result in a presidential majority, or a head of government if the legislative elections result in a parliamentary majority. According to the current Algerian constitutional conception, the executive authority may have a unilateral or bilateral composition, and this is a matter that raises many questions due to the ambiguity and wide academic controversy that it raises because of its direct relationship in influencing the determination of the nature of the Algerian political system as a whole, especially with regard to The principle of political responsibility of the executive branch? !!.